2017
DOI: 10.1016/j.alcohol.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

First description and evaluation of SNPs in the ADH and ALDH genes in a population of alcoholics in Central-West Brazil

Abstract: Worldwide, different studies have reported an association of alcohol-use disorder (AUD) with different types of Single Nucleotide Polymorphisms (SNPs) in the genes for aldehyde dehydrogenase (ALDH) and alcohol dehydrogenase (ADH). In Brazil, there is little information about the occurrence of these SNPs in the AUD population and an absence of studies characterizing the population in the Central-West Region of Brazil. Actually, in Brazil, there are more than 4 million people with AUD. Despite the major health h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Edenberg et al found significant associations between ADH4 rs1984362, rs4699718, rs3762894, rs4148886, rs4699714, rs7694646, rs1126672, DWSHpy188I, rs1042364, rs1042365, rs2602866, and rs2602846 and alcoholism [ 101 ]. The association of ADH4 rs1042364 was replicated in AUD patients from Central-West Brazil [ 102 ]. In addition, ADH4 rs1800759 was related to the early stages of metabolism, whereas ADH4 rs2032349 and rs1573495 were associated with the elimination rate [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Edenberg et al found significant associations between ADH4 rs1984362, rs4699718, rs3762894, rs4148886, rs4699714, rs7694646, rs1126672, DWSHpy188I, rs1042364, rs1042365, rs2602866, and rs2602846 and alcoholism [ 101 ]. The association of ADH4 rs1042364 was replicated in AUD patients from Central-West Brazil [ 102 ]. In addition, ADH4 rs1800759 was related to the early stages of metabolism, whereas ADH4 rs2032349 and rs1573495 were associated with the elimination rate [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 Throughout the past decades, pioneering studies support that the aberrant expression of ALDHs is related to several human non-tumor diseases, for example, Alzheimer's disease (AD) 6 and alcohol intolerance, 7 which are caused by the loss of activity or deficiency of enzyme expression and accumulation of toxic aldehydes. Another ALDH-related disorder is caused by ALDH gene mutations, especially single-nucleotide polymorphisms, 8 contributing to enzyme inactivation, cellular dysfunction, interruption of normal metabolic pathways, and susceptibility to human diseases, such as Sjögren-Larsson syndrome (SLS) and hyperprolinemia type II (HPII). Polymorphisms within these genes may differentially affect the risk of disease development across the ethnic groups evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods for SNP genotyping, including MALDI‐TOF mass spectrometry, Taqman probe, restriction fragment length polymorphism (RFLP), microarray, and DNA sequencing . Due to the high cost, MALDI‐TOF mass spectrometry, microarray, and DNA sequencing are not suitable for analysis of large samples.…”
Section: Introductionmentioning
confidence: 99%